PENGGUNAAN BEBERAPA MEDIA DAN PEMUPUKAN NITROGEN PADA PEMBIBITAN KELAPA SAWIT - Astutik Astutik; Fauzia Hulopi; Ahmad Zubaidi (Universitas Tribhuwana Tunggadewi, 2011)
The quality of palm oil is determined by the quality of land and seeds from the seedling. The Selection of seedling media is an important factor to support the development of the seedlings until the seedlings can be planted into the field. The study aims to determine the effect of several types of seedling media and nitrogen fertilization on the growth of palm oil seedlings. The study was conducted at field experiment of Tribhuwana Tunggadewi University with height of 523 m above sea level, for 4 months. The research used Randomized Block Design with three replication (RAK) of factorial with factor 1: seedling medium (M) consisted of: M1 = soil:sand (1:1), M2 = soil:manure (1:1) and M3 = soil:sand: manure (1:1:1). Factor 2 was the nitrogen fertilizer dosage comprising 4 levels of the nitrogen fertilizer: 0 g (U0), 5 g (U1), 10 g (U2) and 15 g (U3), so there were 12 combinations of each treatment was repeated 3 times. Observations were made at high parameters of seed, seed stem diameter, leaf number, leaf area, and total dry weight of seed. The results obtained that the using of media types interact with nitrogen fertilization in supporting the growth of seedlings (stem diameter). The best oil palm seed obtained in the medium of sand: soil:manure (M3) with 15 g of urea fertilizer per seed was able to produce the largest stem diameter (0.37 cm) up to age 2 months. Separately, 15 g urea nitrogen fertilization produces the best seeds (number of leaf, leaf large, and top dry weight), while the best seedling media was the mixed media of soil:sand:manure